Amine molecular cages as supramolecular fluorescent explosive sensors: a computational perspective - Zwijnenburg,MA; Berardo,E; Peveler,WJ; Jelfs,KE (Journal of Physical Chemistry B, 2016)
We investigate using a computational approach the physical and chemical processes underlying the application of organic (macro)molecules as fluorescence quenching sensors for explosives sensing. We concentrate on the use of amine molecular cages to sense nitroaromatic analytes, such as picric acid and 2,4-dinitrophenol, through fluorescence quenching. Our observations for this model system hold for many related systems. We consider the different possible mechanisms of fluorescence quenching: Förster resonance energy transfer, Dexter energy transfer and photoinduced electron transfer, and show that in the case of our model system, the fluorescence quenching is driven by the latter and involves stable supramolecular sensor–analyte host–guest complexes. Furthermore, we demonstrate that the experimentally observed selectivity of amine molecular cages for different explosives can be explained by the stability of these host–guest complexes and discuss how this is related to the geometry of the binding site in the sensor. Finally, we discuss what our observations mean for explosive sensing by fluorescence quenching in general and how this can help in future rational design of new supramolecular detection systems.